2014
DOI: 10.1128/genomea.00045-14
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequence of Prokaryotic Microbiota from an Intermediate-Salinity Pond of a Saltern in Isla Cristina, Spain

Abstract: Marine salterns are artificial multipond systems designed for the commercial production of salt by evaporation of seawater. We report here the metagenomic sequence of the prokaryotic microbiota of a pond with intermediate salinity (21% total salts) of a saltern located in Isla Cristina, Huelva, southwest Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Analysis of the average community composition of the four solar salterns showed that the most highly represented genus was Haloquadratum which made up 23.6 % of the total archaeal pyrosequencing reads, followed by Halorubrum (19.6 %), Haloarcula (16.9 %), and Halonotius (16.6 %). OTUs affiliated with Haloquadratum, retrieved in this study, were similar to those obtained from clone libraries recovered from solar salterns in Tunisia, Mexico, and Spain (Baati et al 2008;Dillon et al 2013;Fernández et al 2014). Halonotius-related pyrosequencing reads shared similarities with Halonotius pteroides isolated from Australian crystallizers and clones recovered from salt crystals processed from Mediterranean seawater (Burns et al 2004;Baati et al 2010).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Analysis of the average community composition of the four solar salterns showed that the most highly represented genus was Haloquadratum which made up 23.6 % of the total archaeal pyrosequencing reads, followed by Halorubrum (19.6 %), Haloarcula (16.9 %), and Halonotius (16.6 %). OTUs affiliated with Haloquadratum, retrieved in this study, were similar to those obtained from clone libraries recovered from solar salterns in Tunisia, Mexico, and Spain (Baati et al 2008;Dillon et al 2013;Fernández et al 2014). Halonotius-related pyrosequencing reads shared similarities with Halonotius pteroides isolated from Australian crystallizers and clones recovered from salt crystals processed from Mediterranean seawater (Burns et al 2004;Baati et al 2010).…”
Section: Discussionmentioning
confidence: 68%
“…When comparing our pyrosequencing data with those obtained from Santa Pola, in which microbiota inhabiting ponds of different salinities (13, 19, 37 %) were investigated, Haloquadratum was the most represented archaeal genus in the ponds of Bingöl (25 % salinity) and Santa Pola (37 % salinity). The abundance of OTUs related with Halorubrum and Haloquadratum were notable within the ponds of Tuzlagözü (20 % salinity) and Santa Pola (19 % salinity) both of which also contained Halomicrobium-, Natronomonas-, Halobacterium-, and Haloferax-related OTUs which constituted a lower proportion of the pyrosequencing reads (Ghai et al 2011;Fernández et al 2014). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The recruitment of the complete genome of strain M19-40 T (29) from metagenomic data sets recently obtained from hypersaline habitats with different salt concentrations (15,30,31) was carried out via BLASTN analysis. A restrictive cutoff of 95% identity in at least 50 bp was established to guarantee that only similarities at the level of nearly identical microbes were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial DNA from the Santa Pola salterns has recently been sampled and sequenced (Fernandez et al, 2013), in addition to microbial DNA from salterns in Isla Cristina, Spain (Fernández et al, 2014b); Cahuil, Chile (Plominsky et al, 2014); and Chula Vista, California (Rodriguez-Brito et al, 2010). Metagenomics has also made it possible to study the vast haloviral populations that inhabit these ecosystems.…”
Section: Introductionmentioning
confidence: 99%